Field and experimental investigations of an outbreak of African swine in Nigeria (2005)
An African swine fever (ASF), characterized by a mortality reaching 50 to 100 p. 100 in different herds were diagnosed with high domestic pigs loose in Delta State in Nigeria in August 1998. The etiologic confirmation of the PPP was obtained by virus isolation, PCR and sequencing of 280 base pairs a segment of the gene encoding the major protein (VP72) capsid. The experimental infection of animals with infected blood caused fevers, with the highest peaks two to four days after infection, death followed five to six days after infection. Post-mortem examinations revealed very extensive bleeding and the appearance of congested and edematous tissue. The lymph nodes, spleen, liver and kidneys exhibited pronounced random focal necrosis and loss of cells in the follicles of the spleen and lymphoid tissue. Pigs have also revealed acute orchitis with massive neutrophilic infiltrates and macrophages in intertubular connective tissues. of meningitis and focal hemorrhages were observed in the brain and spinal cord. It seems that the home came from the spread east of the PPA, from Benin, neighboring state where the PPP had declared the previous year (1997)